Low levels of knowledge on the assessment of underweight in children and adolescents among middle-grade doctors in England and Wales. Issue 4 (31st January 2013) - Hudson, Lee D; Cumby, Charlotte; Klaber, Robert E; Nicholls, Dasha E; Winyard, Paul J; Viner, Russell M
Abstract : Background: Safe assessment of severe underweight in children is important but experience suggests a frequent lack of understanding. Here we sought evidence from a wide spectrum of trainees. Methods: Cross-sectional telephone survey of an on-call middle-grade paediatric doctor in hospitals providing acute inpatient general paediatric care in England and Wales. Results: Response rate was 100%. Only 50% identified BMI as the appropriate measure for underweight in children. Most did not identify any clinical cardiovascular complications of severe underweight. Only 13% identified corrected QT time (QTc) as an important ECG finding. Knowledge of the refeeding syndrome was poor with 20% unable to define it at all, 21% able to identify some clinical features and 57% aware of potential phosphate abnormalities. Conclusions: Knowledge base among middle-grades doctors in England and Wales on this topic is worryingly poor, particularly in relation to several life-threatening features. Existing and new training approaches should recognise this.